Safety and diagnostic efficacy of cone beam computed tomography-guided transbronchial cryobiopsy for interstitial lung disease: a cohort study. Issue 2 (6th August 2020) - Zhou, Guowu; Ren, Yanhong; Li, Jun; Yang, Ting; Su, Nan; Zhao, Ling; Wang, Dan; Li, Ying; Tian, Zheng; Liu, Ruihong; Dai, Huaping; Wang, Chen
Transbronchial cryobiopsy (TBCB) is one of the most important procedures for assessment of patients with suspected interstitial lung disease (ILD), when diagnosis cannot be made based on clinical and radiological assessments [1–4]. Recent reports suggested that TBCB may offer diagnostic value approaching that of surgical lung biopsy [5, 6]. Cone beam CT (CBCT) can provide 3-dimensional images enabling accurate positioning of cryoprobe. CBCT-guided transbronchial cryobiopsy had a favourable safety profile with low risks of pneumothorax and significant bleeding, with excellent diagnostic yield. https://bit.ly/2WF0SPF